Benign teratoma of neck in adult: a rare case report - Ansari, Mohammed Humaam; Gujrathi, Atishkumar Balajirao; Ambulgekar, Vijayalaxmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Cervical teratomas are extremely rare germ cell tumours. Cervical teratoma is much more common in newborn than adults, and in contrast to the paediatric cases adult teratomas have been highly malignant. Cervical teratoma incorporates lesions arising in the anterior and posterior triangles of the neck. Cervical teratoma can reach enormous size and cause airway obstruction. Surgery is the primary modality of treatment as malignant transformation occurs. Hereby, we present a case of benign teratoma of neck in adult which was completely misdiagnosed preoperatively due to its rare occurence in adults. Even though cervical teratoma of adult is extremely rare, it should be considered as an important differential diagnosis in patient of midline cystic neck swelling. Preoperative radiological investigations requires high index of suspicion. Complete surgical resection is recommended.